Putting the Brakes on Breaks: Osteoporosis Screening and Fracture Prevention - Sarah C. Goode DNP, FNP-C; Jacqueline L. Beshears FNP-BC; Russell D. Goode MD; Theresa F. Wright DNP, RN, CCRC; Anita King DNP, MA, FNP, CDE, FAADE; Brett D. Crist MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2017)
Introduction: This prospective study sought to implement a screening tool to identify and risk stratify at-risk patients for osteoporosis and evaluate patient knowledge of osteoporosis and fragility fractures in an orthopedic trauma clinic affiliated with a level 1 trauma academic center. Methods: Of 297 eligible patients, 291 were screened and risk stratified. Patients completed an osteoporosis screening questionnaire and were risk stratified. Lifestyle advice was given to patients at low fracture risk. A dual-energy X-ray absorptiometry scan was ordered for patients at intermediate fracture risk. A referral was initiated for treatment to a bone health specialist in high fracture risk patients. Twenty patients completed a knowledge-based pretest/posttest. Results: A total of 291 patients were screened, which represented 97.7% of patients over the age of 50. Of those patients, 165 (56.7%) patients met criteria for further osteoporosis evaluation as they were considered either intermediate or high risk for future fractures. One hundred thirty-six (82.4%) patients were referred for bone mineral density evaluation. For the knowledge-based evaluation portion, patients had a 33% gain in knowledge ( P = .0004). The largest knowledge deficit identified pertained to osteoporosis risk factors and lifestyle management. Discussion: The use of an osteoporosis screening questionnaire in the orthopedic trauma clinic produced clinically significant improvement in identification of at-risk patients. A lack of knowledge regarding osteoporosis and fragility fractures was found to exist among these patients. Conclusion: The implementation of an osteoporosis screening tool to identify, risk stratify, and treat patients with osteoporosis and related fragility fractures can be successfully integrated into a busy clinical practice.